INVESTIGATING THE ENGLISH SYLLABUS OF ROOM DIVISION DEPARTMENT RELATED TO THE NEEDS OF THE HOTEL INDUSTRIES: A CASE STUDY AT ONE TOURISM INSTITUTE IN BANDUNG - Handayaningrum, Nuraeni; Setiawan, Budi (Jurnal Pendidikan Bahasa dan Sastra, 2013)
AbstractInvestigating the English Syllabus of Room Division Department Related to the Needs of the Hotel Industries: A Case Study at One Tourism Institute in Bandung. This study investigates what English syllabus needed by the first year students of Room Division Department in one tourism institute in Bandung. In this study, three hotels, 35 fifth semester students of Room Division Department and one English lecturer were involved. The purpose of this study is to find out the Room Division students’ needs in learning English after that to try to propose a new syllabus. The data were collected through questionnaire to the students, interviews with the Front Office Manager of three prestigious hotels in Bandung and one English lecturer. Data from questionnaire and interview were coded and categorized based on the students and hotels’ responses to their needs. The result of this study indicates that there are some shortages of English materials and syllabus that contribute to the students’ performance of English during their job training. Therefore, the writer tries to propose a new syllabus for Room Division Department in this tourism institute.Keywords: ESP, syllabus design, Room Division.Abstrak Investigasi Silabus Bahasa Inggris Divisi Kamar terkait Kebutuhan Industri Perhotelan: Studi Kasus di salah satu Institut Pariwisata di Bandung. Studi ini menginvestigasi silabus Bahasa Inggris yang dibutuhkan oleh mahasiswa tahun pertama program studi Divisi Kamar di salah satu institut pariwisata di Bandung. Studi ini melibatkan 3 hotel, 35 mahasiswa program studi Divisi Kamar semester 5 dan 1 dosen bahasa Inggris. Tujuan dari studi ini adalah untuk mengetahui kebutuhan bahasa Inggris  mahasiswa program studi Divisi Kamar dan juga mencoba mengajukan silabus baru. Data diperoleh melalui kuesioner kepada para mahasiswa, interview dengan Front Office Manager dari tiga hotel di Bandung dan satu dosen bahasa Inggris. Data dari kuesioner dan interview dikategorikan berdasarkan respon yang diberikan oleh para mahasiswa dan Front Office Manager.  Hasil penelitian yang didapat mengindikasikan adanya kekurangan pada materi dan silabus bahasa Inggris yang turut berkontribusi dalam performa mahasiswa dalam menggunakan bahasa Inggris. Berdasarkan data tersebut, peneliti mengajukan silabus baru untuk program studi Divisi Kamar pada institut pariwisata tersebut.Kata kunci: ESP, rancangan silabus, Divisi Kamar.